KEBIJAKAN PENANGGULANGAN KEJAHATAN MELALUI MEDIASI PENAL SEBAGAI ALTERNATIF PENYELESAIAN TINDAK PIDANA KDRT - Liliana Tedjosaputro; Krismiyarsi Krismiyarsi (Jurnal Kriminologi Indonesia, 2012)
Compared to the trial process which only consider legal facts and criminal actions which have been carried out, mediation has the advantage of considering the interests of the future of the family and keep the family together especially for the benefit of the children, religion also teaches the peaceful settlement of disputes. The mediation process is conducted in a closed manner and only attended by related parties and mediator, who is bound with ethics and code of ethics to maintain confidentiality. This process can make criminal avoid jail time, stigmatization, and prison life, which tends to make people become recidivist. Penal mediation has not been widely used for KDRT cases because there is no formal legal protection that provides a strong foundation for the use of penal mediation in the resolution of KDRT cases. Therefore there will be a need to re-evaluate and re-orient the laws, which will lead to the need for a criminal law reform especially concerning KDRT.